Bonus culture: Competitive pay, screening, and multitasking - Roland Bénabou; Jean Tirole (Institute for the Study of Labor (IZA), 2013)
This paper analyzes the impact of labor market competition and skill-biased technical change on the structure of compensation. The model combines multitasking and screening, embedded into a Hotelling-like framework. Competition for the most talented workers leads to an escalating reliance on performance pay and other high-powered incentives, thereby shifting effort away from less easily contractible tasks such as long-term investments, risk management and within-firm cooperation. Under perfect competition, the resulting efficiency loss can be much larger than that imposed by a single firm or principal, who distorts incentives downward in order to extract rents. More generally, as declining market frictions lead employers to compete more aggressively, the monopsonistic underincentivization of low-skill agents first decreases, then gives way to a growing overincentivization of high-skill ones. Aggregate welfare is thus hill-shaped with respect to the competitiveness of the labor market, while inequality tends to rise monotonically. Bonus caps and income taxes can help restore balance in agents' incentives and behavior, but may generate their own set of distortions.
Keywords: D31; D82; D86; J31; J33; L13; M12; 330; incentives; performance pay; bonuses; executive compensation; inequality; multitask; contracts; screening; adverse selection; moral hazard; work ethic; Hotelling; competition